Electricity-enhanced anaerobic, non-photosynthetic mixotrophy by Clostridium carboxidivorans with increased carbon efficiency and alcohol production. (15th January 2022) - Cheng, Chi; Shao, Yingzhi; Li, Weiming; Liu, Jiaxin; Liu, Xiangzhi; Zhao, Yue; Li, Xinqi; Yang, Shang-Tian; Xue, Chuang
Graphical abstract: Highlights: Electricity-enhanced ANP mixotrophy was investigated for the first time. Electricity-enhanced mixotrophy with MV or biochar showed carbon efficiency of >80%. Alcohol/acid ratio of 0.402 mol/mol was achieved with MV and electricity. The carbon efficiency obtained was the highest reported in C. carboxidivorans . Abstract: Anaerobic, non-photosynthetic mixotrophy (ANP mixotrophy) is a process whereby glucose consumption and CO2 fixation via the Wood-Ljungdahl pathway occur concurrently. ANP mixotrophy supplemented with exogenous reducing power and CO2 shows the potential of reducing the carbon loss from glycolysis and enhancing the production of biofuels. Previous studies used H2 and syngas as the exogenous source of reducing power, however, the low solubility of H2 and CO impeded their efficient utilization by bacteria. This study used a bio-electrochemical system (BES) to supply electrons to fix CO2 and shift the metabolite profiles towards more-reduced products in acetogenic bacteria Clostridium carboxidivorans . C. carboxidivorans showed no electroactivity, but the electricity-enhanced fermentation without electron mediator showed higher alcohol production and carbon efficiency compared to open-circuit fermentation. C. carboxidivorans could fix CO2 autotrophically with the electrical current and electron mediator MV or biochar. Electricity-enhanced mixotrophy with MV showed a higher alcohol/acid ratio and carbon efficiency in liquid products (0.402 mol/mol and 82.8%, respectively) compared to those without MV and electricity (0.067 mol/mol and 52.2%, respectively). The addition of biochar in electricity-enhanced mixotrophy increased the carbon efficiency to 80.3%, and promoted the synthesis of butyrate and hexanoate. This study investigated the electricity-enhanced ANP mixotrophic fermentation for the first time, and demonstrated its potential for enhancing carbon efficiency and alcohol production with C. carboxidivorans.